Kinematic Nonlinear Controller for a Miniature Helicopter via Lyapunov Techniques. Issue 3 (26th June 2013) - Salinas, Lucio R.; Slawiñski, Emanuel; Mut, Vicente A.
Abstract This work proposes a kinematic nonlinear controller for an autonomous miniature helicopter that generates saturated reference velocity commands for accurate waypoint trajectory tracking. The control law design is based on a Lyapunov technique with a special choice of the system state equations using spherical coordinates. Stability of the control system is analyzed. Finally, simulation results are presented and discussed, which validate the proposed controller.